FORMULASI DAN EVALUASI KARAKTERISTIK SERUM ANTIOKSIDAN EKSTRAK ETANOL UMBI BIT MERAH (Beta vulgaris L.) - Lia Fikayuniar; Laela Tusyaadah; Anggun Hari Kusumawati; Nurul Hotimah (Jurnal Buana Farma, 2022)
Red Beetroot Tubers have the benefit of providing a natural colour in the manufacture of food products. In the red beetroot fruit, there is the pigment betacyanin which is a derivative of betalain. Betasianin is a red or violet pigment which is a group of polar flavonoids because it binds to nitrogen pigment sugars and is a substitute for anthocyanins. The purpose of this study was to determine which red beet tuber ethanol extract face serum formula (Beta vulgaris L.) was the best, based on the results of the physical evaluation (organoleptic, pH, dispersion, viscosity, homogeneity), proving the presence of antioxidant content based on qualitative testing using KLT and specific spotting (DPPH 0.4%) in each formulation. The result of this study is that the content of secondary metabolites of red beetroot tuber extract (Beta vulgaris L.) positively contains flavonoid compounds, alkaloids, quinones, saponins, and flavonoids, based on the results of the physical evaluation (organoleptic liquid textured and brownish-yellow in colour, pH (5.00), dispersion power (5.5), viscosity (1997), homogeneity test with homogeneous results and based on qualitative antioxidant activity tests using Thin Layer Chromatography and spotting appearance specific (DPPH 0.4%) is F2 because it has a more pronounced yellow spot colour against the background of a purple colour plate, this means that the red beet tuber face serum preparation contains a class of antioxidant compounds. So it can be concluded that the best formula is formula 2 because it has good dosage characteristics and is suspected to contain antioxidant compounds based on qualitative analysis